UNDERSTANDING THE CRUCIAL ROLE OF WOMEN IN SUSTAINABLE DEVELOPMENT PRACTICES - Tyagi, Ruchi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women make significant contributions to the economy through their involvement in various sectors. Many successful businesses are owned and operated by women, some of whom excel in entrepreneurship. These women often possess strong educational backgrounds and apply business theories effectively. It is well-documented that some of the largest and most successful global companies are led by women. In developing countries, numerous women manage small businesses, many of which have proven to be successful. Women entrepreneurs in both developed and developing nations hold considerable social influence, particularly in education and making positive societal impacts. Studying how women's skills in business can be leveraged is essential for fostering a sustainable economy in developing countries.